Differences in physicochemical properties and in vitro digestibility between tartary buckwheat flour and starch modified by heat-moisture treatment. (December 2017) - Xiao, Yao; Liu, Hang; Wei, Ting; Shen, Jing; Wang, Min
Abstract: Native tartary buckwheat starch (NTBS) and native tartary buckwheat flour (NTBF) were modified by heat-moisture treatment (HMT) with different moisture levels (200, 250, 300, and 350 g/kg) to investigate the effect of HMT on their physicochemical properties and in vitro digestibility. Compared to native samples. The onset, peak, conclusion temperatures of HMT-modified samples increased, while the pasting viscosities, enthalpy decreased. After HMT, the gel hardness of starch and flour decreased by 262 and 62.1 g, respectively. But the slowly digestible starch (SDS) content of starch and flour increased by 71.3 and 27 g/kg, respectively, meanwhile the resistant starch (RS) content of starch and flour increased by 23.8 and 41 g/kg, respectively. HMT did not change the A type crystalline pattern of NTBS and NTBF, but the relative crystallinity of NTBS and NTBF increased by 16% and 7%, respectively. HMT had a far greater effect on morphology and pasting properties on flour than on starch. The granule morphology was noticeably changed by HMT, HMT created more cavities and holes on the surface of HMT flours than HMT starches. The results showed that HMT greatly modified the physicochemical properties and in vitro digestibility of NTBS and NTBF to expand their application range. Highlights: Heat-moisture treatment was firstly applied to tartary buckwheat. Heat-moisture treatment decreased pasting viscosities, enthalpy, and gel hardness. Heat-moisture treatment elevated slowly digestibility starch and resistant starch. Heat-moisture treatment improved thermal stability of tartary buckwheat flour. Heat-moisture treatment had a greater effect on morphology of flour than starch.